Cannabis use and cognition in schizophrenia - Løberg, Else-Marie; Hugdahl, Kenneth (Frontiers in Human Neuroscience, 2009)
People with schizophrenia frequently report cannabis use, and cannabis may be a risk factor for schizophrenia, mediated through effects on brain function and biochemistry. Thus, it is conceivable that cannabis may also influence cognitive functioning in this patient group. We report data from our own laboratory on the use of cannabis by schizophrenia patients, and review the existing literature on the effects of cannabis on cognition in schizophrenia and related psychosis. Of the 23 studies that were found, 14 reported that the cannabis users had better cognitive performance than the schizophrenia non-users. Eight studies reported no or minimal differences in cognitive performance in the two groups, but only one study reported better cognitive performance in the schizophrenia non-user group. Our own results confirm the overall impression from the literature review of better cognitive performance in the cannabis user group. These paradoxical findings may have several explanations, which are discussed. We suggest that cannabis causes a transient cognitive breakdown enabling the development of psychosis, imitating the typical cognitive vulnerability seen in schizophrenia. This is further supported by an earlier age of onset and fewer neurological soft signs in the cannabis-related schizophrenia group, suggesting an alternative pathway to psychosis.